2014
DOI: 10.1186/1471-2164-15-1134
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of osmotic sensitive transcription factors in fish intestine via a transcriptomic approach

Abstract: BackgroundTeleost intestine is crucial for seawater acclimation by sensing osmolality of imbibed seawater and regulating drinking and water/ion absorption. Regulatory genes for transforming intestinal function have not been identified. A transcriptomic approach was used to search for such genes in the intestine of euryhaline medaka.ResultsQuantitative RNA-seq by Illumina Hi-Seq Sequencing method was performed to analyze intestinal gene expression 0 h, 1 h, 3 h, 1 d, and 7 d after seawater transfer. Gene ontolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…An extensive and rapid response of the transcriptome to high salinity was found in euryhaline medaka (Oryzias latipes; Wong et al 2014) and Asian sea bass (Lates calcarifer; Xia et al 2013). A high degree of overlap between the genes involved in signalling the osmoregulatory stress response and those related to other stressors such as handling (Wong et al 2014), bacterial infection, and fasting (Xia et al 2013), is consistent with the hypothesis that these signalling networks evolved in parallel. Metabolic pathways were widely repressed in response to stress in Asian sea bass but not in medaka, whereas immune genes were upregulated (particularly those involved in innate immunity) and downregulated in both studies.…”
Section: Short-term Acute Responsessupporting
confidence: 71%
See 1 more Smart Citation
“…An extensive and rapid response of the transcriptome to high salinity was found in euryhaline medaka (Oryzias latipes; Wong et al 2014) and Asian sea bass (Lates calcarifer; Xia et al 2013). A high degree of overlap between the genes involved in signalling the osmoregulatory stress response and those related to other stressors such as handling (Wong et al 2014), bacterial infection, and fasting (Xia et al 2013), is consistent with the hypothesis that these signalling networks evolved in parallel. Metabolic pathways were widely repressed in response to stress in Asian sea bass but not in medaka, whereas immune genes were upregulated (particularly those involved in innate immunity) and downregulated in both studies.…”
Section: Short-term Acute Responsessupporting
confidence: 71%
“…This can make sampling protocols challenging, as any manipulations that fish experience between the environment of interest (whether in the field or laboratory) and the preservation of tissue for RNA extraction can affect gene expression. Depending on the research question, it might be prudent to collect a control sample for handling or transfer stress (e.g., Wong et al 2014) or avoid feeding prior to sampling (e.g., Liu et al 2013). …”
Section: Experimental Protocols and Sampling Designmentioning
confidence: 99%
“…The intestine, a major osmoregulatory organ in fishes, adapts to osmolality in seawater and is involved in gene expression for salinity acclimation (Wong et al . ; Zhang et al . ), but how these processes impact the gut microbiome is still poorly understood.…”
Section: Factors Influencing Fish Gut Microbiome Structurementioning
confidence: 99%
“…Fishes live in dynamic environments where conditions such as temperature, hydrostatic pressure and salinity are highly variable . The intestine, a major osmoregulatory organ in fishes, adapts to osmolality in seawater and is involved in gene expression for salinity acclimation (Wong et al 2014;Zhang et al 2016), but how these processes impact the gut microbiome is still poorly understood. Sullam et al (2012) showed that the majority of fish gut communities clustered with free-living and non-fishassociated microbial assemblages inhabiting similar salinities as their fish host (freshwater vs marine).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…OSTF1 was first identified as a salinity-induced protein in O. mossambicus gills and is orthologous to mammalian TSC22D3 (76,77,95). OSTF1 abundance also increases in other euryhaline teleosts during hyperosmotic stress (96)(97)(98)(99)(100)(101)(102). In addition to changes in mRNA abundance, phosphorylation (103) and alteration of translational preference via microRNA miR-429 (104) have been identified as mechanisms for osmotic regulation of OSTF1.…”
Section: Discussionmentioning
confidence: 99%